Participatory design and evaluation of communication materials on muyong and tapak-tapak systems as indigenous technologies for natural resource management. - Tirol, M. A. C.; Magcale-Macandog, D. B.; Bernardo, E. B. V.; Abucay, E. R.; Talubo, J. P. (2003)
A participatory design and evaluation of information, education, and communication (IC) materials on muyong and tapak-tapak systems as indigenous technologies for natural resource management was conducted among farmers, agricultural technicians, and barangay officials in Amganad and Poblicacion, Banaue, Ifugao. The objectives were to determine the attractiveness, acceptability, and comprehensibility of the communication materials and to find out the effects of the participatory design process among the participants. The IC materials were found to be attractive, acceptable, and comprehensible. A number of constructive comments and suggestions were elicited from the participants to make the necessary revisions to the text and illustrations in the IC materials. While the participatory design process contributed to attractiveness, acceptability, and comprehensibility of the materials, it was found that the materials should be location or community specific. The participants found the participatory design process a highly engaging and learning activity. They felt a sense of pride in seeing their ideas transformed into communication materials. Further, a synergy among experts, semi-technical individuals, and community members could be achieved through participatory design and evaluation.
Keywords: Natural resources management